VASYL STEFANYK IN THE FRENCH LINGUAL READING - Kravets, Yarema (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
French-speaking literary criticism and translation, dedicated to Vasyl Stefanyk, have already more than centenary history. Already in 1912 and 1915 the French reader has known separate novellas of the Ukrainian writer. Since his creative activity has been constantly present in individual Ukrainian monographs which appeared in Swiss, Belgium and France. The most significant publications of the French-speaking Stefanykiana are the book “Croix de pierre” that contained more than 40 writer’s novellas, separate chapters about V. Stefanyk in 12-volume Belgian anthology «Patrimoine littéraire européen» (1993-2000) and Sarcelles’ anthology of the Ukrainian literature of XIth-XXth centuries of NTSH publication in the Western Europe (2004).